Pengaruh diabetes self management education dalam discharge planning terhadap self care behavior pasien Diabetes Mellitus Tipe 2 - Rondhianto, (Jurnal Keperawatan Soedirman, 2012)
Type 2 diabetes is a chronic disease that needed long term treatment. Patient needs self management education to know, to manage and to prevent the complications of the disease. Diabetes self management education (DSME) is one of diabetes education types that can support knowledge, skills and self care abilities, so patient could manage their disease independently. The aims of this research is proving influence of DSME in discharge planning to self care behavior. This research is quasi experiment research with non randomized control group pretest-posttest design. The treatment that given is DSME applied in discharge planning. The result showed that DSME applied in discharge planning effects to self care behavior of type 2 diabetes patient significantly differences between treatment and control group. The t test independent value is 11.919 (p = 0.000). The conclusion of the research is DSME applied in discharge planning can improve self care behavior more significant than usual discharge planning.